Enabling arbitrary wavelength frequency combs on chip. Issue 1 (17th December 2015) - Soltani, Mohammad; Matsko, Andrey; Maleki, Lute
Abstract : A generalized dispersion engineering technique is developed for microresonator‐based Kerr frequency combs. It involves photonic compound ring resonators operating in the strongly dispersive coupling regime intended to achieve anomalous group velocity dispersion at any desirable wavelength ranging from ultraviolet to mid infrared. This technique is promising for on‐chip generation of ultra‐short bright optical solitons. It is validated by exact numerical simulation revealing bright solitons at wavelengths near the rubidium transition (∼794.6 nm) using silicon nitride compound microrings. Abstract: A necessary condition for generation of bright soliton Kerr frequency combs in microresonators is to achieve anomalous group velocity dispersion (GVD) for the resonator modes. This condition is hard to implement in the visible as well as ultraviolet since the majority of optical materials are characterized with large normal GVD in these wavelength regions. We overcome this challenge by borrowing ideas from strongly dispersive coupled systems in solid state physics and optics. We show that photonic compound ring resonators can possess large anomalous GVD at any desirable wavelength, even if each individual resonator is characterized with normal GVD. Based on this concept, we design a mode‐locked frequency comb with thin‐film silicon nitride compound ring resonators in the vicinity of the rubidium D1 line (794.6 nm) and propose to use this optical comb as a flywheel for chip‐scale optical clocks.